The Independence and Impartiality of ICSID Arbitrators Current Case Law, Alternative Approaches, and Improvement Suggestions - Nicole Cleis, Maria (Nijhoff International Investment Law Series, 2017)
In The Independence and Impartiality of ICSID Arbitrators, Maria Nicole Cleis examines the standard of independence required under the ICSID Convention, as evidenced in existing disqualification decisions, and makes novel suggestions for reforms to ensure unbiased decision-making. Readership: All interested in International Investment Law and investor-State arbitration in particular. Readership includes academics, lawyers and arbitrators involved in investment-related disputes (including in-house counsel), treaty negotiators and NGOs.